THE RISE OF ARTIFICIAL INTELLIGENCE (AI)-DRIVEN MARKETING: TRANSFORMING CONSUMER ENGAGEMENT AND PERSONALIZATION. A STUDY OF SELECTED CONSUMERS IN SOUTHEAST, NIGERIA (UNIZIK Journal of Marketing, 2025)
This study investigates the rise of Artificial Intelligence (AI)driven marketing and its transformative effects on consumer engagement and personalization. The primary objectives were to examine the impact of AI-driven marketing on consumer engagement, personalization and challenges in implementation of AI-driven marketing strategies. Data were collected through an online questionnaire distributed via social media and email to ensure wide reach and respondent convenience using a survey of 500 consumer in southeast Nigeria. Content validity was ensured through expert view, The reliability was confirmed with Cronbach’s alpha value above 0.70. Descriptive statistics were used for demographic analysis while multiple regression and ANOVA  the study’s hypotheses and finds reveal a significant positive effects of AI on consumer engagement, satisfaction and purchasing decision Highlighting the need for strategic AI integration to maximize marketing outcome.
Keywords: Artificial intelligence, consumer engagement, personalization, digital marketing, predictive analytics, consumer behavior, and data privacy.